2020
DOI: 10.3390/v13010020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Congenital Cytomegalovirus Infection in Adverse Birth Outcomes: A Review of the Potential Mechanisms

Abstract: Human cytomegalovirus (CMV) is a major cause of nonhereditary adverse birth outcomes, including hearing and visual loss, neurologic deficits, and intrauterine growth retardation (IUGR), and may contribute to outcomes such as stillbirth and preterm delivery. However, the mechanisms by which CMV could cause adverse birth outcomes are not fully understood. This study reviewed proposed mechanisms underlying the role of CMV in stillbirth, preterm birth, and IUGR. Targeted literature searches were performed in PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 52 publications
2
40
0
5
Order By: Relevance
“…It often manifests as a dominant infection in fetuses and infants whose immune system is not yet fully developed, which can lead to damage to multiple organ systems. HCMV infection can lead to placental dysfunction, fetal growth restriction in utero , preeclampsia‐like symptoms, premature delivery, and stillbirth 14 . In the present study, analysis of clinical information revealed that the white blood cell count and protein content in the CSF of neonates in the HCMV‐infected group were significantly higher than those in the control group ( P < 0.05).…”
Section: Discussionsupporting
confidence: 42%
“…It often manifests as a dominant infection in fetuses and infants whose immune system is not yet fully developed, which can lead to damage to multiple organ systems. HCMV infection can lead to placental dysfunction, fetal growth restriction in utero , preeclampsia‐like symptoms, premature delivery, and stillbirth 14 . In the present study, analysis of clinical information revealed that the white blood cell count and protein content in the CSF of neonates in the HCMV‐infected group were significantly higher than those in the control group ( P < 0.05).…”
Section: Discussionsupporting
confidence: 42%
“…Given that other recent reviews have provided thorough overviews of the mechanisms by which CMV might be vertically transmitted 115 117 , here we provide a more focused overview. CMV has been shown to infect trophoblasts, but with substantial gestational age-related differences in infectivity 28 .…”
Section: Torch Pathogensmentioning
confidence: 99%
“…It has been documented that maternal serological status before pregnancy and the timing of maternal HCMV infection during pregnancy (the earlier the infection, the greater the damage of fetal brain) have an impact [ 47 ]. Additionally, HCMV may cause placental damage and dysfunction, including impaired villous growth and differentiation, as well as placental cells apoptosis directly through the viral cytopathic effect or via excessive immune defense [ 48 ]. The placental insufficiency has a negative impact on fetal growth and may be a cause of prematurity during maternal HCMV infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HCMV may cause placental damage and dysfunction, including impaired villous growth and differentiation, as well as placental cells apoptosis directly through the viral cytopathic effect or via excessive immune defense [ 48 ]. The placental insufficiency has a negative impact on fetal growth and may be a cause of prematurity during maternal HCMV infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%